2020
DOI: 10.1016/j.porgcoat.2020.105577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of sulphonamide (Schiff base) ligand and its copper metal complex and their efficiency in polyurethane varnish as flame retardant and antimicrobial surface coating additives

Abstract: This is a repository copy of Synthesis and characterisation of sulphonamide (Schiff base) ligand and its copper metal complex and their efficiency in polyurethane varnish as flame retardant and antimicrobial surface coating additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Recently, [71]. The Schiff base linking unit was also reported to improve the flame retardant properties due to its thermal stability [72]. This research aimed to study the flame retardant properties of hexasubstitutd cyclotriphosphazene compounds containing two Schiff base linking units using the limiting oxygen index (LOI).…”
Section: Effect Of Linking Unit In Flame Retardancy Properties Of Cyclotriphosphazenementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, [71]. The Schiff base linking unit was also reported to improve the flame retardant properties due to its thermal stability [72]. This research aimed to study the flame retardant properties of hexasubstitutd cyclotriphosphazene compounds containing two Schiff base linking units using the limiting oxygen index (LOI).…”
Section: Effect Of Linking Unit In Flame Retardancy Properties Of Cyclotriphosphazenementioning
confidence: 99%
“…ymers 2021, 13, x FOR PEER REVIEW Jamain et al worked on synthesizing a new hexasubstituted cyclotr pound with two Schiff base linking units and containing different te as shown in Figure 3 [71]. The Schiff base linking unit was also repo flame retardant properties due to its thermal stability [72]. This resea the flame retardant properties of hexasubstitutd cyclotriphosphazen taining two Schiff base linking units using the limiting oxygen index ples were prepared with 1 wt.%, and polyester resin was used as mol tained from this study reported that the LOI value increased from 22. ter resin to 24.71% when hexasubstituted cyclotriphosphazene comp rated with polyester resin.…”
Section: Effect Of Linking Unit In Flame Retardancy Properties Of Cyclotriphosphazenementioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] Furthermore, a new Schiff base and its Cu metal complexes have been incorporated into polyurethane varnish and utilized as a multifunctional additive with surface‐coating applications. [ 27 ] Moreover, a Schiff base and its Co (III), Cr (III), and Fe (III) metal complexes were physically incorporated into an epoxy resin and evaluated as antimicrobial, antifouling, flame‐retardant, and corrosion‐resistant additives for paint applications. [ 28,29 ] Antimicrobial sulfonamide ligands and their metal complexes have been prepared and compared with the original ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen index was utilized to evaluate the FR properties of these added substances. [ 10–12 ] Piperidine, phosphaphenanthrene, and triazinetrione groups were simultaneously introduced into the epoxy matrix by chemical linking to get a new intumescent reactive flame retardant epoxy system. [ 13,14 ] Chlorinated, long oil, and styrenated alkyd resins were used as additives to synthetic flame retardant.…”
Section: Introductionmentioning
confidence: 99%